Bioactive components in milk and dairy products - Park, Young W. (Wiley-Blackwell, 2009)
Covers the bioactive components in milk and dairy products of many dairy species including cows, goats, buffalo, sheep, horse, camel, and other minor species. This book discusses bioactive components for manufactured dairy products, such as caseins, caseinates and cheeses; yogurt products; koumiss and kefir; and whey products.